2004
DOI: 10.1039/b311589e
|View full text |Cite
|
Sign up to set email alerts
|

The first SERRS multiplexing from labelled oligonucleotides in a microfluidics lab-on-a-chip

Abstract: The first simultaneous detection of three dye-labelled oligonucleotides in a microfluidics chip by SERRS is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 6 publications
0
69
0
Order By: Relevance
“…Docherty et al [94] reported the SERRS detection of three different dye-labeled DNA oligonucleotides with Escherichia coli sequences in a PDMS microfluidic chip. In this work, the SERRS signals for the mixtures of DNA oligonucleotides and aggregated silver colloids in the channel were measured under static conditions.…”
Section: Biological Analysis and Biomedical Diagnosticsmentioning
confidence: 99%
“…Docherty et al [94] reported the SERRS detection of three different dye-labeled DNA oligonucleotides with Escherichia coli sequences in a PDMS microfluidic chip. In this work, the SERRS signals for the mixtures of DNA oligonucleotides and aggregated silver colloids in the channel were measured under static conditions.…”
Section: Biological Analysis and Biomedical Diagnosticsmentioning
confidence: 99%
“…However, SERRS only occurs with analytes that contain a chromophore with an absorption that matches the wavelength of the excitation source. It has been demonstrated that SERRS can be more sensitive than fluorescence measurements made on standard commercial instrumentation [25], can be successfully applied to microfluidic devices [26], and with the proper Page 4 of 9 chromophores deliver a quantitative analytical method down to 10 -11 M concentrations [27]. Oligosaccharides are another important class of complex biological molecules where SERS has been used for both the identification of closely related species, and the quantitative analysis of oligosaccharides mixtures [28].…”
Section: Sers Of Small Biological Moleculesmentioning
confidence: 99%
“…Approaches to minimise these disadvantages have been reported in the literature. [15] When using inexpensive and disposable PDMS chips the problem can be circumvented, renewing the chip after each measurement. More expensive glass chips can be regenerated by washing steps with aggressive chemicals such as aqua regina or piranha solution after each measurement.…”
Section: Introductionmentioning
confidence: 99%